A case study investigating the effects of an accentuated eccentric load drop jump training program on strength, power, speed and change of direction - Bridgeman, L. A.; McGuigan, M. R.; Gill, N. D. (Sport Performance & Science Reports, 2020)
Previously it has been reported that the use of drop jumps (DJs) improves sprint (1-3), agility (4), 2.4 km time trial(2), jumping (2, 5-8), throwing (9) performance and acute 1RM back squat strength (10). A method which can increase the intensity of a DJ is the addition of load during the eccen-tric portion of the exercise only, termed accentuated eccentric loading (AEL) (11). Previously Bridgeman et al. (12) reported that 5 DJs with an AEL of 20% body mass (BM) resulted in acute enhancements in subsequent countermovement jump (CMJ) jump height and peak power (PP). However, todate, no one has investigated the use of an AEL DJ as part of a longer-term training programme